Legal Analysis of the Serang District Court Decision on Plurium Litis Consortium (Study of Decision Number 81/Pdt.G/2025/Pn Srg) - Masayu, Tiara; Harmonis, Riska; Indrawaeni, Muji; Febriansyah, Dimas (Synergy: Journal of Collaborative Sciences, 2025)
This study provides a juridical analysis of the application of the Plurium Litis Consortium principle in the Serang District Court Decision Number 81/Pdt.G/2025/PN Srg, which declared the plaintiff’s claim inadmissible (niet ontvankelijke verklaard/NO) due to a formal defect in the form of incomplete parties. The legal issue examined concerns the absence of other parties who were proven to have jointly taken and utilized the disputed land but were not included as defendants in the lawsuit. This omission resulted in error in persona, leading to the failure to fulfill the formal requirements of a civil claim. This research employs a normative legal research method using statutory, case, and conceptual approaches to assess the conformity of the judges’ legal reasoning with civil procedural law and relevant jurisprudence. The findings indicate that the judges’ application of the Plurium Litis Consortium principle was appropriate and aligned with the principles of justice, legal certainty, and the effectiveness of judicial decisions. The inclusion of all parties with legal interests in the disputed object is essential to ensure a comprehensive and enforceable judgment. Failure to involve such parties may give rise to subsequent disputes and hinder the execution of the court’s decision. Therefore, the declaration of the claim as inadmissible in the a quo case represents a correct legal measure to preserve the integrity of judicial proceedings and serves as an important guideline for litigants to exercise greater diligence in formulating civil claims in accordance with applicable procedural principles.